Expression profiles of host immune response‐related genes against HEV genotype 3 and genotype 1 infections in rhesus macaques. Issue 8 (30th March 2018) - Choi, Y. H.; Zhang, X.; Tran, C.; Skinner, B.
Summary: Hepatitis E virus (HEV) genotype (gt) 3 infection is food‐borne causing sporadic infections in older individuals and gt1 infection is waterborne, often causing epidemics affecting primarily young adults. Although HEV infection causes self‐limited disease, gt3 induces chronic infection in immunocompromised individuals. Hepatic host gene expression against gt3 infection remains unknown. Host gene expression profiles for HEV gt1 (n = 3) and gt3 (n = 7) infections were analysed in the livers of experimentally infected rhesus macaques. HEV RNA was detected from 2 to 24 days after inoculation (DAI) in stool and serum, elevated alanine aminotransferase (ALT) activity was detected from 7 to 31 DAI, and anti‐HEV antibody became detectable between 12 and 42 DAI. All 10 animals cleared the infection between 34 and 68 DAI. We found that 24%, 48% and 41% of hepatic immune response genes against gt3 infection were upregulated during the early, peak and decline phases of HEV RNA replication. For gt1 infection, 25% of hepatic immune response‐related genes were downregulated during early viremia, but 6%, 34% and 37% of genes were upregulated at the early, peak and during decline of HEV RNA replication, respectively. Our study demonstrated distinct differences in the expression profiles of host immune response‐related genes of HEV gt3 and gt1 infections in experimentally infected rhesus macaques.